Advanced topics in information resources management. - Khosrow-Pour, Mehdi, 1951- (Advanced topics in information resources management series ;, 2005)
Advanced Topics in Information Resources Management is a series of books, which feature the most current research findings in all aspects of information resources management. From successfully implementing technology change to understanding the human factors in IT utilization, these volumes address many of the managerial and organizational applications to and implications of information technology in organizations. Volume 4 presents new concepts in handling and sharing information resources with organizations and individuals worldwide. This book provides insight into and assistance in learning how to successfully implement information resources and technology in the companies, schools, and homes of those who depend upon it.